Kesesuaian Rencana Pelaksanaan Pembelajaran Dengan Pelaksanaan Pembelajaran Pada Mata Pelajaran Pendidikan Agama Islam - Jamaluddin; Hardianto Rahman; Suriyati; Makmur Jaya Nur; Yusniar (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2023)
This study aims: 1) To determine the suitability of the application of lesson plans and lessons in PAI subjects in class XI MIPA 1 SMA Negeri 1 Sinjai Utara; 2) Describe the applicability of lesson plans in the implementation of PAI thematic learning in class XI MIPA 1 students of SMA Negeri 1 North Sinjai. This research uses the Mix Method research method (a research method that combines quantitative and qualitative research which is carried out simultaneously at the same time). Data collection techniques, namely interviews and questionnaires (questionnaire). Data analysis has two stages, namely quantitative data analysis using simple statistical methods in the form of formulations of conformity of lesson plans with implementation of learning and analysis of qualitative data consisting of data reduction, presentation and graphing. conclusion Invest educators in planning, assembling and implementing lesson plans if the learning process reaches its goals. This is evidenced by the acquisition of a questionnaire worth 8.20 with very appropriate criteria. In addition, based on the interview material, it can be described that there is continuity between the Learning Implementation Plan and the implementation of learning, for example in preliminary assignments, core activities and final activities. For quantitative and qualitative data mutually reinforcing, the suitability of the lesson plan for carrying out the study of PAI subjects in class XI MIPA 1 SMA Negeri 1 Sinjai Utara is very suitable.